Generation of Near‐Inertial Currents on the Mid‐Atlantic Bight by Hurricane Arthur (2014). Issue 4 (30th April 2018) - Zhang, Fan; Li, Ming; Miles, Travis
Abstract: Near‐inertial currents (NICs) were observed on the Mid‐Atlantic Bight (MAB) during the passage of Hurricane Arthur (2014). High‐frequency radars showed that the surface currents were weak near the coast but increased in the offshore direction. The NICs were damped out in 3–4 days in the southern MAB but persisted for up to 10 days in the northern MAB. A Slocum glider deployed on the shelf recorded two‐layer baroclinic currents oscillating at the inertial frequency. A numerical model was developed to interpret the observed spatial and temporal variabilities of the NICs and their vertical modal structure. Energy budget analysis showed that most of the differences in the NICs between the shelf and the deep ocean were determined by the spatial variations in wind energy input. In the southern MAB, energy dissipation quickly balanced the wind energy input, causing a rapid damping of the NICs. In the northern MAB, however, the dissipation lagged the wind energy input such that the NICs persisted. The model further showed that mode‐1 waves dominated throughout the MAB shelf and accounted for over 70% of the current variability in the NICs. Rotary spectrum analyses revealed that the NICs were the largest component of the total kinetic energy except in the southern MAB and the inner shelf regions with strong tides. The NICs were also a major contributor to the shear spectrum over an extensive area of the MAB shelf and thus may play an important role in producing turbulent mixing and cooling of the surface mixed layer. Key Points: Spatial variations of near‐inertial currents generated by Hurricane Arthur were mostly related to wind energy input The balance between wind energy input and dissipation determined the damping or persistence of near‐inertial currents Mode‐1 near‐inertial waves contained over 70% of the kinetic energy and were a major contributor to the current shear